Kampung Madinah Temboro as Tablighi Jama῾at Sub-Cultural Community: A Socio-Historical Studies - Kholili Badriza; Muhammad Wildan; Thoriq Tri Prabowo (KARSA Journal of Social and Islamic Culture, 2022)
Temboro, Magetan, is a unique village widely known as Kampung Madinah. The nickname comes from the Islamic tradition embedded in villagers’ everyday lives, associated with Medina, the Propeth’s city. Further observations show that their Islamic tradition is distinctive, primarily referring to the community’s affiliation with the transnational Tablighi Jama’at movement. This fact implies that the community has its worldviews, moral values, and lifestyle, which puts them into a sub-cultural community category. This research examines the socio-historical aspect of Kampung Madinah Temboro as Tablighi Jama’at Sub-Cultural Community between 1984 and 2009. Therefore, we employ historical inquiries and social approaches as methods. We discover that: 1) Pesantren al-Fatah and Markaz Temboro play their central roles in forming Kampung Madinah as a subcultural community based on the Tablighi Jama’at ideology; 2) The subcultural indicators appear in how they dress, how they interact, symbols in the environment, the values they hold, and the integration of the Tablighi Jama’at ideology into people’s daily activities; and 3) Both the Pesantren al-Fatah and the Tablighi Jama’at Markaz networks increase the probability of similar subcultural community emerging elsewhere.